INHERITANCE OF VALUABLE ECONOMIC CHARACTERS IN F1 PLANTS OBTAINED AS A RESULT OF CROSSING THE THIN FIBER VARIETY OF COTTON AND THE LARGE BORE LINES - B. K. Madartov; F. R. Abdiev; N. A. Narimanova; N. U. Mavlonova (Web of Journals Publishing, 2024)
In this paper, the inheritance of valuable economic traits in F1 plants obtained from cross-breeding of fine fiber cotton and large boll lines was analyzed. In the conducted researches, it was observed that the dominance coefficient of cotton was inherited in a positive intermediate, negative intermediate, dominant and extremely dominant state. In order to maintain a positive state of heterosis in the F1 plants obtained as a result of hybridization, it is necessary to continue genetic-selection scientific research in the next generations.
Keywords: cultivar, line, crossbreeding, progeny, valuable economic traits, cotton boll weight, fiber length, fiber yield, dominance level, superdominant, dominant, intermediate inheritance.